Investigating Configuration-Induced Changes in Hybrid Microgrid (HµG) Parameters for Grid-Connected and Standalone Modes - Abraham O. Amole; Owomano N. Imarhiagbe; Stephen Oladipo; Yanxia Sun (International Transactions on Electrical Energy Systems)
The integration of renewable energy sources into hybrid microgrids (HµGs) holds the potential to improve grid voltage profiles, but without proper optimization, it can also lead to performance degradation. This study offers an explorative investigation into the dynamic behavior of HµGs under various configurations, operating in both grid-connected and standalone modes. Through technical analyses, an energy system design is presented for comparing performance across different scenarios. In contrast to previous research, HµGs incorporating solar photovoltaic (PV) systems, wind turbine generation (WTG), diesel generators (DG), and battery energy storage systems (BESS) are modeled. Two operational cases—grid connected (Case 1) and standalone (Case 2)—are simulated, each evaluated through three scenarios using MATLAB/Simulink. Key parameters such as HµG voltage, frequency, power contributions, and battery state of charge (SoC) are analyzed, revealing significant challenges and insights into system behavior. The study shows that changes in system configuration impact HµG voltage and frequency, with maximum deviations reaching 54 Hz, 17 kV, and 5.8 kV. Frequency instability is observed in scenarios involving WTG integration, while sensitivity analysis highlights the critical role of load variations on frequency stability. This research provides actionable benchmarks for network planners and operators to ensure efficient integration of renewable energy into power grids.